Development and applications of a sequential, minimal, radial basis function (RBF) neural network learning algorithm - Lu, Ying Wei. (2010)
This thesis presents a new sequential learning algorithm for realizing a minimal Radial Basis Function (RBF) neural network, referred to as M-RAN (Minimal Resource Allocation Network). Unlike most of the classical RBF neural networks with the number of hidden neurons fixed apriori, the network structure is dynamic in the proposed M-RAN algorithm.